Ansiedad y funcionalidad familiar en estudiantes de la carrera Medicina Humana de la Universidad Nacional de Loja - Quintanilla Barba, Marivy Alexandra (2022)
Anxiety is a mental illness with a significant prevalence result, affecting the capacity and productivity in the work; Its high incidence in the active working population makes it a public health problem. The purpose of this work was to identify the degrees of anxiety, determine the degree of family functionality according the sex and age, also to establish the relationship between anxiety and family functionality in students from the first to the tenth cycle of the Medicine career at Universidad Nacional de Loja. With a quantitative approach, of prospective cross-sectional cohort, with a sample of 241 students, to whom the "Hamilton" anxiety test and "FF-SIL" family functionality were applied, obtaining among the most significant data that the largest number of cases of anxiety they were mild 62.2% (n=150) with a moderately functional family 40.6% (n=98). The group with the highest degree of severe anxiety 21.8% (n=37), moderate 17% (n=29) and the highest level of family dysfunction 21.7% (n=37) were women between the ages of 17 to 23 years. When relating the variables, a p value of less than 0.05 was obtained, which allows us to establish that there is no statistical significance between anxiety and family functionality. Concluding that family functionality is not always related to the degree of anxiety that students present